Centenarians´ quality of life and the role of health and living context - Brandão, Daniela (2019)
Introduction: The interest of the scientic community to study the centenarian population has been growing due to the signicant expansion of life expectancy and human longevity. Evidences about their quality of life (QoL) are, nevertheless, still limited. Different conceptualizations of QoL, the overvaluation of the negative aspects of advanced age and the heterogeneity of the oldest old are some issues that could explain the difculties in this assessment. Objectives: This study aims to analyze the perceived QoL in a sample of centenarians and analyze if there are significant life context (community vs institutional) and health (objective and subjective perception) differences. Methods: A subsample of 59 Portuguese centenarians who participated in the PT100_Oporto Centenarian Study, conducted in 2013 was considered. Descriptive and chi-square analysis were conducted. Results: Most centenarians perceived their QoL in a very positive manner (50.8% rated it as “good”, 6.8% as “very good” and 3.4% as “excellent”); 28.8% perceived it as “acceptable” and 10.2% as “bad”. No significant statistical differences were found for the considered variables. Conclusions: Centenarians seem to present high levels of perceived QoL, which can be associated with a great ability to adapt to adverse situations that occur through their lives. Neither contextual and health aspects seem to inuence the perception of QoL in this particular sample study. Nonetheless, more research is needed to understand the specicities of the QoL in the centenarian population, namely the role of psychological and social variables.